The Type II Protein Secretion System of Legionella pneumophila Promotes Growth at Low Temperatures - Söderberg, Maria A. (American Society for Microbiology, 2004)
The gram-negative bacterium Legionella pneumophila grows in both natural and man-made water systems and in the mammalian lung as a facultative intracellular parasite. The PilD prepilin peptidase of L. pneumophila promotes type IV pilus biogenesis and type II protein secretion. Whereas pili enhance adherence, Legionella type II secretion is critical for intracellular growth and virulence. Previously, we observed that pilD transcript levels are greater in legionellae grown at 30 versus 37°C. Using a new pilD::lacZ fusion strain, we now show that pilD transcriptional initiation increases progressively as L. pneumophila is grown at 30, 25, and 17°C. Legionella pilD mutants also had a dramatically reduced ability to grow in broth and to form colonies on agar at the lower temperatures. Whereas strains specifically lacking type IV pili were not defective for low-temperature growth, mutations in type II secretion (lsp) genes greatly impaired the capacity of L. pneumophila to form colonies at 25, 17, and 12°C. Indeed, the lsp mutants were completely unable to grow at 12°C. The growth defect of the pilD and lsp mutants was complemented by reintroduction of the corresponding intact gene. Interestingly, the lsp mutants displayed improved growth at 25°C when plated next to a streak of wild-type but not mutant bacteria, implying that a secreted, diffusible factor promotes low-temperature growth. Mutants lacking either the known secreted acid phosphatases, lipases, phospholipase C, lysophospholipase A, or protease grew normally at 25°C, suggesting the existence of a critical, yet-to-be-defined exoprotein(s). In summary, these data document, for the first time, that L. pneumophila replicates at temperatures below 20°C and that a bacterial type II protein secretion system facilitates growth at low temperatures.